2005
DOI: 10.1007/s10832-005-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties of Sol-Gel Derived BaTi4O9 and Ba2Ti9O20:B2O3 Ceramics

Abstract: BaTi 4 O 9 and B 2 O 3 -doped Ba 2 Ti 9 O 20 ceramics powders have been prepared by a sol-gel route. The phase evolution, grain size and dielectric properties of the BaTi 4 O 9 and Ba 2 Ti 9 O 20 -based ceramics powders have been investigated. These results show that the BaTi 4 O 9 and 5 wt% B 2 O 3 -doped Ba 2 Ti 9 O 20 ceramics powders calcined at 800 • C for 2 h with the grain sizes of 30-80 and 50-200 nm, respectively. Monophase sample of BaTi 4 O 9 with orthorhombic symmetry could be obtained after the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…From Table I, it is observed that the electric permittivity (I» ranges from 35 to 41, the Q factor from 2950 to 3400, the temperature coefficient (Tf) from 6.2 to 10.2 ppmrC, and the overall tunable frequency range of 5.12-6.95 GHz. Some results are in agreement with those obtained by Tang [7], although their samples were sintered at quite higher temperatures (> 1200°C).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…From Table I, it is observed that the electric permittivity (I» ranges from 35 to 41, the Q factor from 2950 to 3400, the temperature coefficient (Tf) from 6.2 to 10.2 ppmrC, and the overall tunable frequency range of 5.12-6.95 GHz. Some results are in agreement with those obtained by Tang [7], although their samples were sintered at quite higher temperatures (> 1200°C).…”
Section: Methodssupporting
confidence: 89%
“…However, during the sintering treatment, reactions between the glass and ceramics may induce compositional changes and/or development of second phases due to local heterogeneities, 978-1-4799-1397-8/13/$31.00 ©2013 IEEE which may deteriorate the microwave dielectric properties [1][2][3][4]. To minimize these drawbacks several preparation methods have been used [4][5][6][7][8][9][10]. In this study a new approach for obtaining B20radded BTO nanopowder is considered by using a hybrid chemical and co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optical transparency in the crystallized sample is most likely caused by smallness of crystallizing-BaTi 4 O 9 phase, which suppress the scattering of incident light. Furthermore, this glass-ceramics is considered to be a possible functional material, because the BaTi 4 O 9 possesses a photocatalytic activity and a high-Q dielectric which was reported 3220 [7,8]. Consequently, the transparent BaTi 4 O 9 -nanocrystallized glass obtained in this study has a great possibility for optically/dielectrically-functional material.…”
Section: Electroceramics In Japan XIVmentioning
confidence: 78%
“…There have been relatively fewer investigations [8,9] of the chemical processing methods such as hydrothermal, sol-gel, and precipitation processes for producing ceramics for microwave applications. Most of the microwave dielectric materials are being produced by conventional solid-state reaction process.…”
Section: Introductionmentioning
confidence: 99%